Characterization of water droplets size distribution in aviation turbine fuel: ultrasonic homogeniser vs high shear speed mixer - Ugbeh-Johnson, Judith; Carpenter, Mark; Okeke, Nonso Evaristus; Mai, Nathalie (Elsevier, 2023)
Pumps, pressure drops across fittings, and flight operations (such as turning manoeuvres, take-off, and landing) are some of the many sources of turbulence mixing and shearing in aircraft fuel systems, therefore, making it an inevitable condition. Literature established that shearing conditions would influence the droplets and droplets size distribution in an oil/water emulsion. So, low intensity shearing conditions could be beneficial as it promotes droplets coalescence, which could be a driving force for a weak emulsion. However, to date no experimental data has shown the influence homogenising intensity and total water content has on dispersed water droplets size distribution in aviation fuel. Therefore, to expand knowledge of quantification of measurements of dispersed water droplets in aviation fuel, this study characterizes dispersed water droplets in aviation turbine fuel, varying available laboratory homogenising devices and water content. Results presented show that droplets count increases with water concentration and shearing effect. To provide more statistical evidence, kurtosis and skew values were calculated from the extrapolated data and compared with data from a hexanol/water mixture given that hexanol is likely to form a stable emulsion. Experimental results show that the higher the homogenising intensity the more stable the emulsion is likely to be with a higher kurtosis and skew value close to that for the hexanol/water mixture. Therefore, observations show that mild shearing conditions (high shear mixing in this case) could help promote droplets coalescence, leading to a better separation ability.
Keywords: Droplets size; Stokes law; Aviation fuels; Fuel systems; Shedding; Jet fuel; Aircraft; Emulsion